STRATEGI KEBIJAKAN PENINGKATAN DAYA SAING PRODUK INDONESIA MELALUI PEMBENTUKAN KAWASAN EKONOMI KHUSUS (KEK) - Soesilowati, Etty; ., Widiyanto (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
This research was intended (1) to conduct deep examinations on the preparedness of KEK (Special Area for Economic Activity) infrastructures and the related institutions for investors. (2) to conduct the relevant cost-benefit analyses. This research employed quantitative and qualitative approaches. The analyses showed that there were really infrastructure supports (a sea harbor for exports, roads of national class, by pass, a tolled highway, railroads, an international airport and ample electricity), vendor supports (3,339 big- and medium-size industries, 644,000 small industries, a metal industrial center, 524 manufacturers and 873 export-oriented industries) and human resource supports (9 State-owned Colleges, 332 Private Colleges, 782 Vocational High Schools, 19 Private Work Training Centers and 2 State-owned Work Training Centers). Based on an assumption of an average price of Rp. 45,000/m for land and an average cost of Rp. 60,000/nT for filling out 2-meter deep coastal areas, it can be concluded that the recommended project should be continued because it has positive cashflows and net-cashflows as well as relatively high B/C ratio (19 kali). However, it has a relatively long waiting time for ROI (at least 25 years) and small IRR (7.7%).